Study on the detection method of holes in composite insulator rods. Issue 5 (4th March 2021) - Zhang, Sida; Cheng, Li; Liu, Yunfan; Liao, Ruijin; Wang, Tingting; Huang, Huan
Abstract: The holes in composite insulator rods are a type of quality defects. However, not all holes can be identified by the dye penetration test according to existing standards and some holes can cause abnormal heating of the composite insulator during operation. Micro‐computed tomography is used to study the structure of these holes. Based on the pore structure, the holes are classified as dependent or independent. The dependent hole is formed by several interconnected adjacent pores and the overlong equivalent penetration path makes it cannot be effectively identified by the standard dye penetration test. Considering the structure of the dependent hole, ethanol gas was used to increase the effectiveness of the dye penetration test. The experimental results show that the detection rate of dependent holes is approximately 80% as the ethanol concentration is close to saturation, and the porosity can be inferred based on the number of penetration points.